К вопросу о парламентских и президентских выборах в Армении (Հայաստանում նախագահական և խորհրդարանական ընտրությունների խնդրի շուրջ) - Ալիխանյան Մարիամ (YSU Journal of International Affairs, 2017)
The matter of the organization of communications during the elections provides with the solutions of several problems. It depends on how effectively political parties will organize their relations with electors. The main forms of communication which have been used by political parties in the process of federal elections since Armenia’s independence have been observed in the article. Special attention has been paid to the matter of Parliamentary elections of 2017 as they were a transition from a kind of a political system into another. The article observes the new forms of communications in the elections which were offered by the political parties in the elections of 2017.